Wilt Disease of Shisham (Dalbergia sissoo Roxb.) - Bakshi, B. K.; Singh, Sujan (Indian Forester, 1954)
This is the first in the series of articles dealing with the wilt disease of shisham, the localities of occurrence of the disease, its symptoms, the fungus causing wilt and its life-history, the occurrence and effects of the fungus on the host. A detailed summary is given at the end.